Taking industrial action - a legal guide - Owen, Nerys (London, 2017)
"UK laws on industrial action were already some of the most restrictive in the developed world before the draconian Trade Union Act 2016 came into force. On 1 March 2017 that Act, described by the TUC as “the most serious attack on the rights of trade unions and their members in a generation”, introduced an extra layer of restrictions on balloting, notice and picketing. This booklet aims to help union reps and negotiators understand the restrictions, navigate them and discover what they can do within those confines. It also looks at other types of action unions are taking to meet their objectives in helping members improve their pay and conditions when a dispute arises."